Biopolymers in Aerobic Granular Sludge—Their Role in Wastewater Treatment and Possibilities of Re-Use in Line with Circular Economy - Agnieszka Cydzik-Kwiatkowska (MDPI AG, 2021)
Aerobic granular sludge (AGS) technology for wastewater treatment ensures better quality effluent and higher process sustainability than wastewater treatment systems based on activated sludge. One of the reasons for the better operational results of AGS systems is the high content of extracellular polymers (EPS) in the granule structures. EPS produced during granulation have a very complex composition with a predo minance of polysaccharides and proteins, and one of the main components, alginate, may have a wide variety of practical applications. This review summarizes up-to-date information on the composition of EPS in AGS, the manner in which their production and composition are affected by the operational parameters of wastewater treatment, and the effects of EPS in biomass on wastewater treatment and sludge management. Additionally, the possibility of polymer recovery from AGS is presented together with information regarding potential applications based on the newest findings. Re-use of AGS-derived polymers will increase the sustainability of wastewater treatment processes by making them more economical and reducing the amount of sludge that requires management.